This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Michael Ng isn't this a great generalisation of one of the special cases for ramanujan's formula for infinite nested radicals?
I didn't understood that why u put 3 in the last.
Log in to reply
It's so that the right side would match the expression in the question.
Ramanujan 's formula
as seen in image
putting
x=2
and
n=1
,
=x+n
=2+1
=
3
Let f(x) be 1 + x 1 + ( x + 1 ) 1 + . . . . . . . . . .Note that f ( x ) 2 = x ∗ f ( x + 1 ) + 1 . Through observation, f(x)=x+1. Question is nothing else but f(2) i.e 2+1=3
Why f(x)^2=x.f(x+1)+1?
Log in to reply
Hello, The one who posted solution was me (now my previous account is deleted) .
What I did was considering f(x) to be the expression as written in solution ,then f(x+1) is what inside the second square root.
I thought the f(x) particularly what is written above because if we can find the f(x), then f(2), would be easy to find and that is what is required.
f ( x ) = 1 + x f ( x + 1 ) This was the result i got, and to my surprise the solution to this functional equation was apparent and easy x+1.
Though after one year ,unknowingly today when i solved this problem, i too used Ramanujan's way. BTW is the solution clear?
Log in to reply
It was a easy guess that the solution of the functional equation is x+1 but can you provide a proper proof so as to find the the solution of the functional equation without hit and trial??? @Mayank Chaturvedi
Through observation? How ? The function you found is vague, you have f(x)^2 and f(x+1), how did you connect these two?
It's Impossible\
Problem Loading...
Note Loading...
Set Loading...
Let's start with forming a nested radical expression for x : ∣ x ∣ = x 2 = 1 + ( x − 1 ) ( x + 1 ) = 1 + ( x − 1 ) 1 + x ( x + 2 ) = 1 + ( x − 1 ) 1 + x 1 + ( x + 1 ) ( x + 3 ) In the same way if we continue indefinitely,we get the following nested radical expression for x : ∣ x ∣ = 1 + ( x − 1 ) 1 + x 1 + ( x + 1 ) 1 + ( x + 2 ) 1 + ( x + 3 ) ⋯ By observation this expression fits the form of the question,so simply put x = 3 to get: 3 = 1 + 2 1 + 3 1 + 4 ⋯